2017
DOI: 10.1007/s11657-017-0407-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of serum vitamin D levels in Romania

Abstract: The prevalence of vitamin D deficiency is high, particularly in the elderly. The data show a strong seasonal variation of serum 25(OH)D in all subgroups of our Romanian population with highest levels in September and lowest levels in March.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
35
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 26 publications
11
35
3
1
Order By: Relevance
“…As we all know, vitamin D3 is needed from not only adequate intake from diet or supplements but also biosynthesis in the skin in response to su cient exposure to sunlight. Several studies have concerned seasonal variation in serum 25(OH)D concentrations [29,30,31]. This study also found that serum 25(OH)D concentration was the lowest in January and the highest in July and August.…”
Section: General Characteristics Of Participant Womensupporting
confidence: 58%
“…As we all know, vitamin D3 is needed from not only adequate intake from diet or supplements but also biosynthesis in the skin in response to su cient exposure to sunlight. Several studies have concerned seasonal variation in serum 25(OH)D concentrations [29,30,31]. This study also found that serum 25(OH)D concentration was the lowest in January and the highest in July and August.…”
Section: General Characteristics Of Participant Womensupporting
confidence: 58%
“…As we all know, vitamin D3 is needed from not only adequate intake from diet or supplements but also biosynthesis in the skin in response to sufficient exposure to sunlight. Several studies have concerned seasonal variation in serum 25(OH)D concentrations [29,30,31]. This study also found that serum 25 intake of vitamin D compensated for decreased ultraviolet radiation B exposure [34].…”
Section: General Characteristics Of Participant Womensupporting
confidence: 56%
“…(a) comparison of the vitamin D levels in cases without ED versus with ED (subgroup vitamin D detection methods); (b) comparison of the vitamin D levels in cases without ED versus with ED (subgroup sample size >1,000 and sample size <1,000); (c) comparison of IIEF-5 score in cases without vitamin D deficiency versus with vitamin D deficiency (subgroup vitamin D detection methods); (d) comparison of IIEF-5 score in cases without vitamin D deficiency versus with vitamin D deficiency (subgroup sample size >100 and sample size <100) intake and sun exposure (latitude, climate, personal or cultural habits of sun bathing, clothing). Generally, the serum vitamin D concentrations vary with season in subjects of all age, being lowest during winter and early spring, highest in summer (Niculescu et al, 2017). Only one study has provided the differential seasonal data (Sudarevic et al, 2017); we were unable to perform this specific analysis based on this seasonal variation, because most study failed to provide the related data.…”
Section: Discussionmentioning
confidence: 94%
“…Generally, the serum vitamin D concentrations vary with season in subjects of all age, being lowest during winter and early spring, highest in summer (Niculescu et al, 2017). (a) comparison of the vitamin D levels in cases without ED versus with ED (subgroup vitamin D detection methods); (b) comparison of the vitamin D levels in cases without ED versus with ED (subgroup sample size >1,000 and sample size <1,000); (c) comparison of IIEF-5 score in cases without vitamin D deficiency versus with vitamin D deficiency (subgroup vitamin D detection methods); (d) comparison of IIEF-5 score in cases without vitamin D deficiency versus with vitamin D deficiency (subgroup sample size >100 and sample size <100) intake and sun exposure (latitude, climate, personal or cultural habits of sun bathing, clothing).…”
Section: Discussionmentioning
confidence: 99%